THE ANALYSIS OF CONSUMER BEHAVIOR OF MILLENNIALS AND Z GENERATION TRAVELING IN JAPAN DURING THE COVID-19 PANDEMIC - Asep Parantika (JELAJAH: Journal of Tourism and Hospitality, 2021)
The study aims to analyze the consumer behavior of domestic travelers in Japan, especially the Millennial and Z generation groups during the Covid-19 pandemic. Fears of exposure and the imposition of a state of emergency, making tourists both domestic and foreign cancel their trips. Economic downturn amid the threat of the spread of a pandemic that is not yet known when it will end, it becomes a challenge for Japanese society to adjust to existing conditions. The Japanese government issued the "Go to Travel Campaign" program, a campaign aimed at stimulating the travel of domestic tourists who are down due to the spread of Covid-19. However, strict health protocols are in place to prevent and control the spread of the virus. This research was conducted using a qualitative descriptive approach by sharing questions and conducting interviews to analyze consumer behavior, especially millennials and Z groups, identifying behaviors that can change the tourism industry to understand its needs. Through an analysis of consumer behavior of millennial and Z generation groups in Japan during the Covid-19 pandemic, it was obtained that they were highly motivated and dared to travel in the pandemic and were not afraid of Covid-19, although in the pandemic the Millennial and Z groups always use masks and all their activities are in the crowd because their style always follows and adheres to health protocols that are followed by the Japanese government. By having an understanding and sensitivity or adjustment of the behavior of consumer travelers, it will make it easier for manufacturers to identify the needs of travelers indicated by purchasing decisions as a mirror of the behavior of travelers.